Laser pulse treatment method for improving corrosion resistance of cupronickel alloy and cupronickel alloy
The amorphous layer is formed on the surface of the copper alloy by laser pulse treatment, which solves the corrosion resistance of the copper alloy in the corrosion environment, and significantly improves its intergranular corrosion resistance and corrosion resistance.
Patent Information
- Application Number
- CN202411681011.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-22
- Publication Date
- 2025-02-21
- Estimated Expiration
- 2044-11-22
AI Technical Summary
Copper alloys are prone to electrochemical corrosion in environments containing strong oxidative anions, and in corrosion environments such as seawater, acid and alkaline media, the grain boundaries are more likely to corrode than in the crystal, resulting in a decrease in corrosion resistance.
The surface of the copper alloy is cleaned, heated and quickly cooled by laser pulse treatment to form an amorphous layer with a thickness of 1-10 μm. This method forms a disordered, randomly distributed amorphous layer through non-contact heating of the laser and rapid cooling of low-temperature inert gases, avoiding the existence of grains and grain boundaries.
The corrosion resistance and corrosion resistance of copper alloys are significantly improved. In 3.5% NaCl solution, the corrosion resistance rate is reduced by at least 30% and the surface hardness is increased by at least 50%.
Smart Images

Figure CN119491176A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of material engineering, and in particular to a laser pulse processing method for improving the corrosion resistance of white copper alloy and white copper alloy. Background Art
[0002] Traditional nickel silver alloy is a copper-nickel alloy with excellent corrosion resistance. It is one of the most widely used corrosion-resistant metal materials. Nickel silver has better resistance to seawater erosion, and because of its good forming and welding performance and thermal conductivity, it is widely used in ships. Among them, nickel silver BFe10-1-1 and BFe30-1-1 alloys have a wide passivation range and good corrosion resistance. They are called "marine engineering alloys" and are one of the indispensable materials for condensers such as seawater desalination, coastal power stations, and ships. However, due to the long-term exposure of nickel silver to Cl-containing -1 , O 2- , S 2- Electrochemical corrosion is still inevitable in highly oxidizing anion environments. At the same time, the alloy inevitably contains other alloying elements or impurities during the smelting preparation process, which will also affect its corrosion resistance. In addition, after long-term exposure to corrosive environments such as seawater and acidic and alkaline media, the grain boundaries of the material are more susceptible to corrosion than the grains, and intergranular corrosion occurs. Therefore, improving the corrosion resistance of white copper alloy is one of the hot scientific and technological problems at home and abroad, and it is of great significance to important industrial fields such as seawater purification, ship design, and chemical engineering.
[0003] Generally speaking, there are mainly microalloying and surface coating methods to improve the corrosion resistance of white copper alloy. Among them, microalloying refers to adding alloying elements such as Fe, Mn, Zn, Al, and rare earth to white copper alloy to improve the electrochemical corrosion performance of the alloy, or improve the passivation film formation ability of the alloy to improve the corrosion resistance of the alloy. However, adding alloying elements cannot fundamentally solve the problem of intergranular corrosion resistance. Surface coating of the alloy can isolate the alloy from external corrosion (such as patent CN202211483322.7, a method for improving the corrosion resistance of white copper alloy pipes; CN202410202037.6, high hardness nickel-free electrolytic corrosion resistant coating structure and preparation method thereof), but the bonding performance between the coating and the alloy substrate will affect the corrosion resistance effect.
[0004] In view of this, the present application provides a laser pulse processing method for improving the corrosion resistance of white copper alloy, so as to solve the technical problem of improving the corrosion resistance of white copper alloy. Summary of the invention
[0005] The purpose of the present application is to provide a laser pulse processing method and a white copper alloy for improving the corrosion resistance of white copper alloy, so as to solve the above-mentioned problems.
[0006] To achieve the above objectives, this application adopts the following technical solutions: A laser pulse processing method for improving the corrosion resistance of white copper alloy, comprising: The surface of the white copper alloy is cleaned, then heated by a laser heater, and then quickly cooled by a cooling medium.
[0007] Preferably, the nickel silver alloy is pre-machined or polished, and the surface roughness is Ra1.6 to Ra0.8.
[0008] Preferably, the surface cleaning adopts one or more of mechanical cleaning, acid cleaning, plasma cleaning, and laser surface cleaning, with the goal of removing oil stains, impurities or other coverings on the alloy surface.
[0009] Preferably, the laser heater includes one or more of a CO2 laser, a Nd:YAG laser, a semiconductor laser and an excimer laser.
[0010] Preferably, the power of the laser heater is 1-10 kW, and the light source of the laser heater is 2-50 mm away from the surface of the white copper alloy.
[0011] Preferably, when the laser heater performs the heating, the scanning direction is parallel to the surface of the white copper alloy, and the scanning speed is 100-1000 mm / min.
[0012] Preferably, the number of scans is 2-10 times.
[0013] Preferably, the cooling medium includes one or more of high-pressure nitrogen, high-pressure helium, liquid nitrogen and liquid helium.
[0014] Preferably, during the rapid cooling, the cooling rate of the surface of the white copper alloy is not less than 1×10 4 °C / s; After each heating, the rapid cooling is performed at least once.
[0015] The present application also provides a white copper alloy, which is prepared using the laser pulse processing method for improving the corrosion resistance of the white copper alloy.
[0016] Compared with the prior art, the beneficial effects of this application include: The laser pulse processing method for improving the corrosion resistance of white copper alloy provided in the present application uses a laser to quickly scan the surface of white copper alloy, and then uses a low-temperature inert gas to quickly blow and scan, so that the metal with a thickness of 1-10μm on the surface of the white copper alloy is rapidly melted under the non-contact heating of the laser, and then rapidly cooled under the action of the low-temperature inert gas to form an amorphous layer with a thickness of 1-10μm. This amorphous layer has the same chemical composition as the matrix, but the atoms therein are in a disordered and randomly distributed state, without the grain boundaries of traditional crystal materials, and does not contain dislocations, grain boundaries, twins, vacancies, stacking faults and other crystallographic defects. Therefore, this amorphous layer does not have the difference in the position of the grain boundary within the crystal. On the one hand, it can protect the surface of the alloy, hinder the penetration of ions in the environment, and improve its resistance to intergranular corrosion; on the other hand, the amorphous layer is easily passivated to form a dense passivation layer, which improves the corrosion resistance of the alloy. This method can significantly improve the corrosion resistance of the alloy without changing the chemical composition, and has the same chemical composition as the matrix, without affecting the performance and use of the material matrix.
[0017] This method is highly applicable to white copper alloy pipes, plates or other surfaces of various shapes, thicknesses and specifications.
[0018] The white copper alloy provided in the present application is prepared by the above method, which fundamentally solves the problem of intergranular corrosion resistance and has excellent corrosion resistance. In a 3.5% NaCl solution, the corrosion rate at room temperature can be reduced by at least 30%; the surface hardness can be increased by at least 50%. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope of the present application.
[0020] Figure 1 A schematic flow chart of a laser pulse processing method for improving the corrosion resistance of white copper alloy provided in an embodiment; Figure 2 Schematic diagram of laser heating; Figure 3 This is an EBSD photograph of the longitudinal section boundary of the B10 white copper alloy obtained in Example 1 after laser surface treatment; Figure 4 This is an EBSD photograph of the longitudinal section boundary of the white copper alloy obtained in Comparative Example 1; Figure 5 This is the EBSD photograph of the longitudinal section boundary of the white copper alloy obtained in Comparative Example 2. DETAILED DESCRIPTION
[0021] The embodiments of the present application will be described in detail below in conjunction with specific examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. If specific conditions are not specified in the examples, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0022] Example 1 like Figure 1 As shown, this embodiment provides a laser pulse processing method for improving the corrosion resistance of B10 white copper sheet, which specifically includes the following steps: (1) Surface cleaning of white copper alloy The surface roughness of the B10 nickel silver alloy sheet after machining or polishing reaches Ra1.6.
[0023] Mechanical polishing is used to remove oil, impurities or other coverings on the alloy surface.
[0024] (2) Laser heating like Figure 2 As shown, a 2.0KW CO2 laser heater is used to quickly scan the surface of the cupronickel within a range of 2-3mm from the surface. The scanning speed is 100mm / min and the number of repetitions is 2 times.
[0025] (3) Inert gas rapid cooling Nitrogen was used to rapidly cool the surface of the copper-nickel alloy after laser heating, so that the cooling rate of the copper-nickel alloy surface reached 1×10 4 ℃ / s, cooling once after each laser heating.
[0026] (4) Performance testing like Figure 3 As shown, a 2 μm thick amorphous layer is formed on the surface of the white copper alloy.
[0027] In 3.5% NaCl solution, the corrosion rate without treatment is 0.012g / m 2 h, after treatment, it is reduced to 0.007g / m 2 h, the corrosion rate at room temperature can be reduced by 41.6%.
[0028] The surface hardness increased from HV118 to HV210, an increase of 78%.
[0029] Example 2 This embodiment provides a laser pulse processing method for improving the corrosion resistance of B10 white copper sheet, which specifically includes the following steps: (1) Surface cleaning of white copper alloy The surface roughness of the B10 nickel silver alloy sheet after machining or polishing reaches Ra0.8.
[0030] Mechanical polishing is used to remove oil, impurities or other coverings on the alloy surface.
[0031] (2) Laser heating A CO2 laser heater with a power of 10.0KW was used to quickly scan the surface of the cupronickel at a distance of 45-50mm. The scanning speed was 1000mm / min and the number of repetitions was 4 times.
[0032] (3) Inert gas rapid cooling Nitrogen was used to rapidly cool the surface of the copper-nickel alloy after laser heating, and the cooling rate of the copper-nickel alloy surface reached 2×10 4 ℃ / s, after each laser heating, cooling was performed 4 times.
[0033] (4) Performance testing An amorphous layer with a thickness of 6 μm was formed on the surface of the white copper alloy.
[0034] In 3.5% NaCl solution, the corrosion rate without treatment is 0.012g / m 2 h, after treatment, it is reduced to 0.006g / m 2 h, the corrosion rate at room temperature can be reduced by 50.0%.
[0035] The surface hardness increased from HV120 to HV221, an increase of 84.1%.
[0036] Example 3 This embodiment provides a laser pulse processing method for improving the corrosion resistance of B10 white copper pipe, which specifically includes the following steps: (1) Surface cleaning of white copper alloy The surface roughness of the B10 nickel-nickel alloy pipe after machining or polishing reaches Ra0.8.
[0037] Use alcohol + acetone to clean and remove oil, impurities or other coverings on the alloy surface.
[0038] (2) Laser heating A 4.0KW CO2 laser heater was used to quickly scan the cupronickel surface at a distance of 10-15mm from the surface. The scanning speed was 600mm / min and the number of repetitions was 4 times.
[0039] (3) Inert gas rapid cooling Nitrogen was used to rapidly cool the surface of the copper-nickel alloy after laser heating, so that the cooling rate of the copper-nickel alloy surface reached 1×10 4℃ / s, after each laser heating, cooling was performed 4 times.
[0040] (4) Performance testing A 3 μm thick amorphous layer is formed on the surface of the white copper alloy.
[0041] In 3.5% NaCl solution, the corrosion rate without treatment is 0.014 g / m 2 h, after treatment, it is reduced to 0.008 g / m 2 h, the corrosion rate at room temperature can be reduced by 42.8%.
[0042] The surface hardness increased from HV115 to HV206, an increase of 79.1%.
[0043] Example 4 This embodiment provides a laser pulse processing method for improving the corrosion resistance of B30 white copper sheet, which specifically includes the following steps: (1) Surface cleaning of white copper alloy The surface roughness of the B30 nickel silver alloy sheet after machining or polishing reaches Ra0.8.
[0044] Use alcohol + acetone to clean and remove oil, impurities or other coverings on the alloy surface.
[0045] (2) Laser heating A 4.0KW CO2 laser heater was used to quickly scan the cupronickel surface at a distance of 12-15mm from the surface. The scanning speed was 500mm / min and the number of repetitions was 4 times.
[0046] (3) Inert gas rapid cooling Nitrogen was used to rapidly cool the surface of the copper-nickel alloy after laser heating, so that the cooling rate of the copper-nickel alloy surface reached 1×10 4 ℃ / s, cooling 3 times after each laser heating.
[0047] (4) Performance testing A 2 μm thick amorphous layer is formed on the surface of the white copper alloy.
[0048] In 3.5% NaCl solution, the corrosion rate without treatment is 0.013 g / m 2 h, after treatment it is reduced to 0.007 g / m 2 h, the corrosion rate at room temperature can be reduced by 46.1%.
[0049] The surface hardness increased from HV110 to HV203, an increase of 84.5%.
[0050] Comparative Example 1 Different from Example 1, the cupronickel alloy was heated and air-cooled (cooling rate was approximately 80-100°C / min) using a common heating method (common resistance heating, maximum temperature 800°C, heat preservation for 30 min). The microstructure of the grains at the surface is shown in FIG. Figure 4 As shown. Compared with Example 1 ( Figure 3 ) Compared with the sample that was rapidly heated and cooled by laser, the surface of the cupronickel alloy that was heated by ordinary means did not have an amorphous layer and only contained ordinary grains.
[0051] The experiment was conducted by using the method of ordinary heating + rapid cooling. It was found that the grain microstructure at the surface of the white copper alloy was different from Figure 4 Similarly, no amorphous layer appears.
[0052] Comparative Example 2 The copper-nickel alloy was heated by the same laser heating method as in Example 1, but air cooling (cooling rate was approximately 80-100°C / min) was used for cooling. The microstructure of the grains at the surface is shown in FIG. Figure 5 As shown. With the embodiment ( Figure 3 ) Compared with the sample that was rapidly heated and cooled by laser, some fine grains appeared on the surface of the white copper alloy that was cooled by air cooling, but there was no amorphous layer.
[0053] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.
Claims
1. A laser pulse processing method for improving the corrosion resistance of white copper alloy, characterized in that: include: The surface of the white copper alloy is cleaned, then heated by a laser heater, and then quickly cooled by a cooling medium.
2. The laser pulse processing method for improving the corrosion resistance of white copper alloy according to claim 1, characterized in that: The white copper alloy is pre-machined or polished, and the surface roughness is Ra1.6 to Ra0.
8.
3. The laser pulse processing method for improving the corrosion resistance of white copper alloy according to claim 1, characterized in that: The surface cleaning adopts one or more of mechanical cleaning, acid cleaning, plasma cleaning and laser surface cleaning.
4. The laser pulse processing method for improving the corrosion resistance of white copper alloy according to claim 1, characterized in that: The laser heater includes one or more of a CO2 laser, a Nd:YAG laser, a semiconductor laser and an excimer laser.
5. The laser pulse processing method for improving the corrosion resistance of white copper alloy according to claim 4, characterized in that: The power of the laser heater is 1-10KW, and the light source of the laser heater is 2-50mm away from the surface of the white copper alloy.
6. The laser pulse processing method for improving the corrosion resistance of white copper alloy according to claim 4, characterized in that: When the laser heater performs the heating, the scanning direction is parallel to the surface of the white copper alloy, and the scanning speed is 100-1000 mm / min.
7. The laser pulse processing method for improving the corrosion resistance of white copper alloy according to claim 6, characterized in that: The number of scans is 2-10 times.
8. The laser pulse processing method for improving the corrosion resistance of white copper alloy according to claim 1, characterized in that: The cooling medium includes one or more of high-pressure nitrogen, high-pressure helium, liquid nitrogen and liquid helium.
9. The laser pulse processing method for improving the corrosion resistance of white copper alloy according to any one of claims 1 to 8, characterized in that: During the rapid cooling, the cooling rate of the surface of the white copper alloy is not less than 1×10 4 °C / s; After each heating, the rapid cooling is performed at least once.
10. A white copper alloy, characterized in that: The invention is prepared by using the laser pulse processing method for improving the corrosion resistance of white copper alloy as described in any one of claims 1 to 9.
Citation Information
Patent Citations
A method for improving the corrosion resistance of white copper alloy pipe
CN115786752B
High-hardness nickel-free electrolytic corrosion-resistant coating structure and preparation method thereof
CN118147716A
Method for preparing amorphous layer of bulk material on surface of magnesium alloy
CN109266980A
Accurate preparation method of ultra-fine grain structure thin-wall conical part
CN114260330A
Method for refining surface grains of CuCr alloy part
CN115074647A